EDUKASI MENSTRUASI DAN CARA MENGATASI PERMASALAHANYA DI RUMAH BELAJAR UMMU JASMINE BANTUL YOGYAKARTA - Sujono Riyadi; Dwi Yati; Retno Sumiyarini (LPPM STIKES Madani, 2022)
Adolescence is a transition period in the human life span that connects childhood and adulthood. Adolescent girls during puberty have several problems including the development of feminine attitudes, physical changes, menstrual cycle conditions, acne, obesity and even disease. The purpose of this community service is to increase the knowledge of teenagers studying at the Umm Jasmine Learning House Bantul Yogyakarta on problems related to menstruation and how to solve them. The method used is in the form of lectures and discussions as well as showing videos about menstruation to stimulate the level of knowledge of adolescents. The results obtained are the level of knowledge of adolescents is in the medium category 45.45% and the level of knowledge is high in the majority that is equal to 54.54%. The majority of adolescent information sources related to menstruation were obtained from mothers as parents by 18.92%, the second highest knowledge came from teachers at schools who provided information related to menstruation by 45.45% and a small proportion of adolescents who received information related to menstruation from the internet by 9.09%. The conclusion in this observation is that there is an increase in the level of knowledge of adolescents after providing education about menstruation.